Structural Shocks and Political Participation in the US - Marina Chugunova; Klaus Keller; Sampsa Samila (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
This paper examines the impact of the large structural shocks – automation and import competition – on voter turnout during US federal elections from 2000 to 2016. Although the negative income effect of both shocks is comparable, we find that political participation decreases significantly in counties more exposed to industrial robots. In contrast, the exposure to rising import competition does not reduce voter turnout. A survey experiment reveals that divergent beliefs about the effectiveness of government intervention drive this contrast. Our study highlights the role of beliefs in the political economy of technological change.
Keywords: D72; J23; F16; 330; automation; trade; labor demand; voter turnout